Factor Structure of the Russian Version of the Somatic Symptom Scale-8 (SSS-8) - A.A. Zolotareva (Консультативная психология и психотерапия, 2022)
The Somatic Symptom Scale-8 (SSS-8) is one of the most common and psychometrically sound instruments for self-reporting somatization and eight specific somatic symptoms [7]. Objective. This study was aimed to adapt and examine the factor structure of the Russian SSS-8. Methods. A total sample of 167 care home residents completed the Russian version of the SSS-8 and questionnaire covering socio-demographic information. Results. Exploratory and confirmatory factor analyses showed that the adapted scale demonstrated a single-factor structure evaluating the somatization total score via medically unexplained symptoms (stomach or bowel problems; back pain; pain in arms, legs, or joints; headaches; chest pain or shortness of breath; dizziness; feeling tired or having low energy; trouble sleeping). The Cronbach’s α coefficient for the SSS-8 total score was 0,76, indicating the good internal consistency. Conclusions. The Russian version of the SSS-8 is a reliable and valid measure assessing somatic symptoms in care home residents.